Psychometric Properties of Rapid Word-Based Rate Measures in the Assessment of Bulbar Amyotrophic Lateral Sclerosis: Comparisons With Syllable-Based Rate Tasks. - Shellikeri, Sanjana; Marzouqah, Reeman; Brooks, Benjamin Rix; Zinman, Lorne; Green, Jordan R.; Yunusova, Yana (Journal of Speech, Language & Hearing Research, 2021)
Purpose: Rapid maximum performance repetition tasks have increasingly demonstrated their utility as clinimetric markers supporting diagnosis and monitoring of bulbar disease in amyotrophic lateral sclerosis (ALS). A recently developed protocol uses novel real-word repetitions instead of traditional nonword/syllable sequences in hopes of improving sensitivity to motor speech impairments by adding a phonological target constraint that would activate a greater expanse of the motor speech neuroanatomy. This study established the psychometric properties of this novel clinimetric protocol in its assessment of bulbar ALS and compared performance to traditional syllable sequence dysdiadochokinetic (DDK) tasks. Specific objectives were to (a) compare rates between controls and speakers with symptomatic versus presymptomatic bulbar disease, (b) characterize their discriminatory ability in detecting presymptomatic bulbar disease compared to healthy speech, (c) determine their articulatory movement underpinnings, and (d) establish within-individual longitudinal changes. Method: DDK and novel tongue ("ticker"--TAR) and labial ("pepper"--LAR) articulatory rates were compared between n = 18 speakers with presymptomatic bulbar disease, n = 10 speakers with symptomatic bulbar disease, and n = 13 healthy controls. Bulbar disease groups were determined by a previously validated speaking rate cutoff. Discriminatory ability was determined using receiver operating characteristic analysis. Within-individual change over time was characterized in a subset of 16 participants with available longitudinal data using linear mixed-effects models. Real-time articulatory movements of the tongue front, tongue dorsum, jaw, and lips were captured using 3-D electromagnetic articulography; effects of movement displacement and speed on clinimetric rates were determined using stepwise linear regressions. Results: All clinimetric rates (traditional DDK tasks and novel tasks) were reduced in speakers with symptomatic bulbar disease; only TAR was reduced in speakers with presymptomatic bulbar disease and was able to detect this group with an excellent discrimination ability (area under the curve = 0.83). Kinematic analyses revealed associations with expected articulators, greater motor complexity, and differential articulatory patterns for the novel real-word repetitions than their DDK counterparts. Only LAR significantly declined longitudinally over the disease course. Conclusion: Novel real-word clinimetric rate tasks evaluating tongue and labial articulatory dysfunction are valid and effective markers for early detection and tracking of bulbar disease in ALS.